Electronic and magnetic properties of 4d series transition metal substituted graphene: A first-principles study. (August 2017) - Sun, Minglei; Ren, Qingqiang; Zhao, Yiming; Chou, Jyh-Pin; Yu, Jin; Tang, Wencheng
Abstract: We implement a theoretical study of the geometry parameters, binding energies, electronic and magnetic properties of 4d series transition metals substituted graphene. Based on a hybridization model, the variations of binding energies and magnetic moments size can be well understood. According to the occupation of different vacancy-metal hybridized electronic states, the substituted systems can be divided into three types: (i) for Y and Zr, all the bonding states are completely occupied, and the magnetic moment is zero; (ii) for Nb, Mo and Tc, nonbonding states become occupied, which induce a strong localized magnetic moment with d character of 1 μ B, 2 μ B and 1 μ B, respectively; (iii) for Ru, Rh and Pd, the magnetic moment oscillates between 0 and 1 μ B as the antibonding state become occupied. In addition, we found that the Y- and Rh-substituted graphene exhibit metallic behavior, and the semiconducting natures were found in Zr-, Ru- and Pd-substituted systems. More interestingly, half-metallic state were predicted in Nb- and Tc-substituted graphene, while spin-polarized semiconducting state is realized in Mo-substituted system. The Curie temperature of about 83, 354 and 36 K was estimated for Nb-, Mo- and Tc-substituted systems in the mean-field approximation at impurity concentration 3.125%. Graphical abstract: